Impact of negative energy balance and postpartum diseases during the transition period on oocyte quality and embryonic development in dairy cows - Serbetci, Idil; González-Grajales, L. Antonio; Herrera, Carolina; Ibanescu, Iulian; Tekin, Muhittin; Melean, Manuel; Magata, Fumie; Malama, Eleni; Bollwein, Heinrich; Scarlet, Dragos (Frontiers in Veterinary Science, 2024)
Transition period is a critical time for dairy cows because a large proportion of clinical and subclinical diseases are observed in the first month after parturition. Occurrence of negative energy balance is associated with depressed immunity and these conditions can affect oocyte quality and further embryonic development. The aim of this study was to assess the effects of negative energy balance-associated disorders on in vitro embryo production (IVP) in dairy cattle. We hypothesized that subclinical metabolic and/or inflammatory disorders have a negative effect on oocyte developmental competence and morphokinetic parameters of the resulting embryos. The study was conducted on 30 lactating Holstein-Friesian cows which were assigned into four groups: healthy (HEAL, n = 6), metabolic disease (META, n = 8), inflammatory disease (INFL, n = 8), or combined metabolic and inflammatory disease (COMB, n = 8). Ovum pick-up (OPU) was performed twice weekly on all cows over a period of four weeks (n = 8 OPU sessions/cow) starting on the fifth week postpartum, and the collected oocytes were subjected to routine IVP. Donor's health status did not affect the number of oocytes/OPU or the recovery rate (p>0.05). The number of quality 1 oocytes collected from INFL and COMB cows was lower compared to HEAL cows (p<0.05). Also, the percentage of quality 1 embryos was reduced in META and COMB compared to HEAL cows (p<0.05). Cleavage, blastocyst and hatching rates were similar among groups (p>0.05). Presence of disease did not affect the time required by zygotes to reach specific developmental stages, as recorded by means of time-lapse monitoring. Nevertheless, there was a higher probability of direct cleavage after IVF in oocytes of COMB cows compared to those of HEAL cows (p<0.05). In conclusion, oocytes and embryos derived from dairy cows diagnosed with subclinical metabolic and/or inflammatory diseases during the transition period showed reduced quality but similar developmental potential and morphokinetics when compared to healthy cows. These results shed light on the consequences of subclinical disease on embryonic development in dairy cows which might be important for embryo transfer programs.